From Solo to the Palace: The Anatomy of Political Communication in the Formation of Jokowi's Dynasty - Aisyah A, Siti; Nurfiadi, Hasib; Az-Zahro, Fatimah Dury; Najib, M.; Hayat, Akbar Muzahid; Abdurrasyied, Muhammad Hasyied (Institut Agama Islam Negeri (IAIN) Manado, 2024)
The issue of political dynasties has increasingly emerged in democratic systems, including in Indonesia. The political dynasty of Jokowi's family is interesting to analyze as it demonstrates how political communication can be strategically implemented in building a positive image and gaining broad public support. This research aims to examine how Jokowi's family's political communication shapes the image of their political dynasty. The theories used are political communication and framing. This research employs a qualitative descriptive approach to illustrate political communication in forming a positive image of Jokowi's family political dynasty. Data was obtained through literature studies utilizing various sources such as books, scientific journals, research reports, magazines, and other related research articles. The analysis used in this research is content analysis by analyzing textual, visual, or symbolic data to identify meaning. This research is limited to the period from the beginning of Jokowi's career as Mayor of Solo until the formation of his family's political influence at the national level, particularly approaching the 2024 Election. This research finds two main political communication strategies: through family political regeneration and consistent framing use. The researchers found that the political success of Jokowi's family demonstrates the effectiveness of planned and long-term-oriented political communication strategies. Through portraying themselves as a family close to the people, both through direct and symbolic messages, they have successfully built public trust, which became the key to consecutive victories in various elections, both by Jokowi himself and his family members.